Pengembangan Aplikasi Edukasi Game Little Iqra Berbasis Android Menggunakan Metode MDLC - Rezha Mulia Revandy; Yuma Akbar (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2022)
Conventional learning methods have decreased in effectiveness during this pandemic period, many teaching staff have difficulty in monitoring the development of their students. Little Iqra is an Android-based educational application that helps schools monitor student progress through fun media for children. This app allows teachers to see their students progress in real time with the Real-Time Score feature powered by Firebase. This application is in the form of a Quiz. In this application, the teacher can change the content displayed on the quiz freely so that the potential for using this application is very large according to the creativity of the teacher. This application was also developed by taking into account the technological needs of all parties, with that this application has advantages in its size, which is 5MB. With this application, a study was conducted to determine behavioral intentions in its use using the Multimedia Development Life Cycle (MDLC) model. This little iqra game is expected to help the teacher in supervising children's development and increasing children's interest in learning.